Organizational Performance Assessment of Search and Rescue Teams: A Collaboration Between Technical Aspects and Service Quality - Tri Nurcahyo Andiantoro; Irawaty Igirisa; Fenti Prihatini Dance Tui (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to develop and test an integrative organizational performance assessment model that combines technical aspects, service quality, and organizational factors. Using a sequential explanatory mixed-method design, data were collected over five months through surveys of 85 SAR personnel (total sampling), 210 service recipients (stratified random sampling), and 25 key informants (purposive sampling). Quantitative data were analyzed with Structural Equation Modeling (SEM) using AMOS 24.0 and SPSS 26.0, while qualitative data were examined through thematic analysis with NVivo 12 and case study validation. The results indicate that technical competence and equipment readiness significantly enhance organizational performance, while service quality dimensions particularly reliability, responsiveness, and empathy play a crucial role in building public trust. Organizational factors moderate the relationship between technical aspects and service quality, underscoring the importance of adaptive leadership, coordination with local agencies, and a learning-oriented culture. The integrated model explains 68.4% of the variance in organizational performance, demonstrating its robustness in capturing SAR effectiveness. Qualitative findings further highlight adaptive strategies under resource constraints, collaboration rooted in local wisdom, gaps between SOPs and operational realities, and the humanistic dimension of rescue operations. This study contributes theoretically by advancing a holistic performance assessment model for SAR organizations and practically by offering evidence-based recommendations for BASARNAS and local SAR units. These include strengthening technical resources, enhancing service delivery systems, improving organizational structures, engaging communities, and aligning SOPs with field realities.